A new Malaysia? constitutional development after the 2018’s general election - Shuaib, Farid Sufian (2019)
After the fourteenth general election in Malaysia in May 2018, a new coalition known as Pakatan Harapan (Alliance of Hope) came to power. It replaced Barisan Nasional (the National Front) that ruled at the federal level since the independence in 1957. In the manifesto of Pakatan Harapan, the coalition promises to rebuild the nation. It promises to embark upon institutional and political reform for a new Malaysia involving the office of the Prime Minister, the Attorney General, Parliament, the judiciary, public service and human rights. Approaching the first year of the new government, it is apt to review its accomplishment in fulfilling the pledges of institutional reforms. It is pertinent to review of this institutional reform processes and to answer the question whether the promised New Malaysia has become a reality.